Myxomycetes de Florianópolis (Santa Catarina - Brasil) Myxomycetes of Florianópolis (State of Santa Catarina - Brazil) - Laise de Holanda Cavalcanti; Silvana Túlio Fortes (Acta Botânica Brasílica, 1994)
Considerando a inexistência de registros de ocorrência de Myxomycetes em Florianópolis, realizou- se coletas nas matas da Lagoa do Peri e Lagoa da Conceição, em 1990, assinalando-se as seguintes espécies : Lycogala exiguum Morg. (Enteridiaceae ); Cribraria languescem Rex, C. vulgaris Sclir. (Cribrariaceae ); Arcyria cinerea ( Bull. ) Pers. , Hemitrichia serpula ( Scop.) Rost., H. calyculata ( Speg.) Farr e Hemitrichia sp (Trichiaceae ); Stemonitis fusca Roth. e S. smithii Macbr. (Stemonitaceae). Exsicatas encontram-se depositadas no herbário UFP. Lycogala exiguum é assinalada pela primeira vez para Santa Catarina, Cribraria languescens para a região Sul e Cribraria vulgaris para o Brasil. O levantamento eleva para 47 o número de espécies referidas para o Estado de Santa Catarina. Fornece-se um histórico do estudo deste qrupo de organismos em Santa Catarina bem como a área de ocorrência de cada espécie no Estado e nas diferentes regiões do Brasil. A survey on Myxomycetes was made in the woods of Lagoa do Peri and Lagoa da Conceição in 1990, considering the absence of reports of this kind for the city of Florianópolis, when the following species were registered: Lycogala exiguum Morg. (Enteridiaceae); Cribraria languescem Rex, C. vulgaris Schr. (Cribrariaceae); Arcyria cinerea (Bull.) Pers. Hemitrichia serpula (Scop.) Rost., H. calyculata (Speg.) Fair and Hemitrichia sp (Trichiaceae); Stemonitis fusca Roth, and S. smithii Macbr. (Stemonitaceae). Exicates are deposited at the herbarium UFP. Lycogala exiguum is noted for the first time in the state of Santa Catarina, Cribraria languescem in the South and Cribraria vulgaris in Brazil. The survey raises up the number of registers refered to the state of Santa Catarina to 47 species. A review of the studies on this group of organisms in Santa Catarina is given as well as the area where each species occur in this state and in different regions of Brazil.